Torção natural em nanotubos de carbono de parede simples - Verçosa, Daniel Gomes (2012)
The next technological revolution comes through advances in nanotechnology, where nanometric materials such as single wall carbon nanotubes (SWNTs) play a very important role. This brand new material, discovery in 1993, has very interesting physical properties, generating great interest in both academic and industrial areas. Recent works have shown that these properties are very sensitive to diferent kinds of deformation, such as axial, radial and torsional strains. In this work we studied theoretically how the electronic strucutre of SWNTs, and therefore their properties, changes in the presence of torsion. We used the extended Tight-Binding model (ETB) to calculate the band structure of the tubes. Torsion is induced through specific constrains which modify the angular component of the primitive vectors of graphene lattice. To obtain the most stable structural configuration we used an optimization method named as modified simple gradient. It was observed that quiral nanotubes presents a non-zero torsion, named natural torsion, in ground state. This torsion decreases with the inverse cube of the tube’s diameter. Also, the dependece of natural torsion on chiral angle varies according with the SWNT metallicity. The optical transition energies for naturally torsioned tubes and non-torsioned tubes are compared and variation up to 50% on the minigap of metallic tubes are observed. Finally, we discussed what are the possible implications due to the presence of a natural torsion on the science of these carbon nanostructures.